Current Applications for the Use of Extracorporeal Carbon Dioxide Removal in Critically Ill Patients. (4th February 2016) - Camporota, Luigi; Barrett, Nicholas
Abstract : Mechanical ventilation in patients with respiratory failure has been associated with secondary lung injury, termed ventilator-induced lung injury. Extracorporeal venovenous carbon dioxide removal (ECCO2 R) appears to be a feasible means to facilitate more protective mechanical ventilation or potentially avoid mechanical ventilation in select patient groups. With this expanding role of ECCO2 R, we aim to describe the technology and the main indications of ECCO2 R.